Impact of “Green Revolution” gene Rht-B1b on coleoptile length of wheat - Xu, Dengan; Hao, Qianlin; Yang, Tingzhi; Lv, Xinru; Qin, Huimin; Wang, Yalin; Jia, Chenfei; Liu, Wenxing; Dai, Xuehuan; Zeng, Jianbin; Zhang, Hongsheng; He, Zhonghu; et al. (Frontiers in Plant Science, 2023)
Wheat coleoptile is a sheath-like structure that helps to deliver the first leaf from embryo to the soil surface. Here, a RIL population consisting of 245 lines derived from Zhou 8425B × Chinese Spring cross was genotyped by the high-density Illumina iSelect 90K assay for coleoptile length (CL) QTL mapping. Three QTL for CL were mapped on chromosomes 2BL, 4BS and 4DS. Of them, two major QTL QCL.qau-4BS and QCL.qau-4DS were detected, which could explain 9.1%–22.2% of the phenotypic variances across environments on Rht-B1 and Rht-D1 loci, respectively. Several studies have reported that Rht-B1b may reduce the length of wheat CL but no study has been carried out at molecular level. In order to verify that the Rht-B1 gene is the functional gene for the 4B QTL, an overexpression line Rht-B1b-OE and a CRISPR/SpCas9 line Rht-B1b-KO were studied. The results showed that Rht-B1b overexpression could reduce the CL, while loss-of-function of Rht-B1b would increase the CL relative to that of the null transgenic plants (TNL). To dissect the underlying regulatory mechanism of Rht-B1b on CL, comparative RNA-Seq was conducted between Rht-B1b-OE and TNL. Transcriptome profiles revealed a few key pathways involving the function of Rht-B1b in coleoptile development, including phytohormones, circadian rhythm and starch and sucrose metabolism. Our findings may facilitate wheat breeding for longer coleoptiles to improve seedling early vigor for better penetration through the soil crust in arid regions.